HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN SUPERVISI KEPALA SEKOLAH SERTA IKLIM KERJA TERHADAP KINERJA GURU DI SMP KECAMATAN CIKANDE KABUPATEN SERANG - Naila Attamimi (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
The purpose of this study to determine:(1) The correlation of transformasional leadership style to the teacher performance at SMP Cikande Force District of Serang Regency (2)the correlation of the leadership supervision to the teacher performance at SMP Cikande Force District of Serang Regency (3).  The correlation of the work climate to the teacher performance at SMP Cikande Force District of Serang Regency?, 4). The correlation of the tranformational leadership style, leadership supervision, and work climate to the teacher performance at SMP Cikande Force District of Serang Regency.This study used quantitative research methods through  surveyquestionnaires.The target population in this study are all teachers,amounting to 75 people in SMP Cikande Force District of Serang Regency and teacher population in SMP Cikande Force District of Serang Regency (selected 4 SMP from 8 SMP at Cikande Force District of Serang Regency) Samples were taken purposive. Data collected by using a questionere. The data were collected then analyzed by using the technique of data analysis simple correlation, multi correlation, coeficient of determination and significance test with SPSS 16.The result showed that (1) The correlation of transformasional leadership style varriable (X1) with teacher performance (Y) is in good category are 0.632 (2) The correlation of leadership supervision(X2) with teacher performance (Y) is in a good category, which is  0,657 (3) The correlation of work climate (X3) with teacher performance (Y) is in sufficient category, which is 0,479 (4) The contribution of transformasional leadership style varriable (X1) and leadership supervision(X2)and work climate (X3) is 0,731.